Konseptualisasi Pendidikan Keluarga berbasis Syariah sebagai Strategi Meningkatkan Ketahanan Keluarga di Era Globalisasi - M Mohsi; Taufik Taufik (Program Pascasarjana UIN Sultan Maulana Hasanuddin Banten, Jalan Jenderal Sudirman No. 30, Serang - Banten 42118, 2023)
This research will focus on sharia-based education, to offer a conceptualization of sharia-based family education as a strategy to increase family resilience. Several formulations will be discussed in this research. First: The concept of sharia-based family education. Second; Sharia-based family education strategy in improving the quality of family resilience. Third: sharia values ​​and principles as the conceptual basis of family education. This research uses a qualitative approach, using literature as the primary source of research. The conceptualization strategy for Sharia-based family education can be carried out by internalizing Islamic values, including internalizing Islamic values, Sharia-based character education, role empowerment, Sharia-compliant gender, Islamic financial education, Islamic-based children's education, parental involvement in education, use Technology Wisely, and a Flexible Approach to Social Change.